Detection of Theileria sp. in Grazing Cattle at Tamangapa Landfill Makassar (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2023)
This study aims to detect the occurrence or absence of Theileria sp. parasitic infection in cattle grazed at the Tamangapa Makassar landfill. This research was conducted in January 2022- February 2023. Many samples used in this study were 43 samples from the total cattle population in the study site of 781 cows. The sample used in this study was blood made by Giemsa staining. The data analysis used in this study is descriptive analysis. The results showed that from 43 samples there were 31 negative samples and 12 samples were positive for Theileria sp. in cattle grazed at the Tamangapa Makassar landfill. This can be seen from observations under a microscope, which is seen the formation of rods or sticks in erythrocyte cells. The positive samples were divided into several categories, based on the sex of the presentation of Theileria sp. cases in female cattle (32.43%) higher than in males (0%). Based on age, the ≥2 (39%) year old category is higher than the